High production of a class III lantipeptide AmfS in Streptomyces griseus. Issue 1 (2nd January 2017) - Takano, Hideaki; Matsui, Yuhei; Nomura, Junpei; Fujimoto, Masahiro; Katsumata, Naoto; Koyama, Takafumi; Mizuno, Isamu; Amano, Shoichi; Shiratori-Takano, Hatsumi; Komatsu, Mamoru; Ikeda, Haruo; Ueda, Kenji
Abstract: AmfS, a class III lantipeptide serves as a morphogen in Streptomyces griseus . Here, we constructed a high production system of AmfS in S. griseus . We isolated S. griseus Grd1 strain defective in glucose repression of aerial mycelium formation and found it suitable for the overproduction of AmfS. Two expression vectors carrying the strong and constitutive ermE2 promoter were constructed using a multicopy number plasmid, pIJ702. The use of the Grd1 strain combined with the expression vectors enabled high production of AmfS by S. griseus into its culture broth. The expression system was also effective for the generation of abundant AmfS derived from Streptomyces avermitilis . In addition, site-directed mutagenesis revealed the amino acid residues essential for the morphogen activity of AmfS. These results indicate that the constructed system enables efficient production of class III lantipeptides by Streptomyces . Graphical abstract: : High production of a class III lantipeptide AmfS in Streptomyces griseus .